Purification and characterization of the stage-specific embryonic enhancer-binding protein SSAP-1. - DeAngelo, D J (1993)
We have demonstrated that a highly conserved segment of DNA between positions -288 and -317 (upstream sequence element IV [USE IV]) is largely responsible for the transcriptional activation of the sea urchin H1-beta histone gene during the blastula stage of embryogenesis. This sequence is capable of acting as an embryonic enhancer element, activating target genes in a stage-specific manner. Nuclear extracts prepared from developmentally-staged organisms before and after the gene is activated all contain a factor which specifically binds to the enhancer. We have purified a 43-kDa polypeptide which binds to and footprints the USE IV enhancer element. We refer to this protein as stage-specific activator protein 1 (SSAP-1). Early in development before the enhancer is active, SSAP appears as a 43-kDa monomer, but it undergoes a change in its molecular weight beginning at about 12 h postfertilization (early blastula) which precisely parallels the increase in H1-beta gene expression. Modified SSAP has an apparent molecular mass of approximately 90 to 100 kDa and contains at least one 43-kDa SSAP polypeptide. Thus, it is the disappearance of the 43-kDa species and the appearance of the 90- to 100-kDa species which coincide with the H1-beta gene activation. The correlation between the change in molecular weight of SSAP and the stage-specific activation of H1-beta gene expression strongly suggests that this higher-molecular-weight form of SSAP is directly responsible for the blastula stage-specific transcriptional activation of the late H1 gene.